2002
DOI: 10.1007/s00442-002-1019-0
|View full text |Cite
|
Sign up to set email alerts
|

CO2 exchange and thallus nitrogen across 75 contrasting lichen associations from different climate zones

Abstract: Aiming to investigate whether a carbon-to-nitrogen equilibrium model describes resource allocation in lichens, net photosynthesis (NP), respiration (R), concentrations of nitrogen (N), chlorophyll (Chl), chitin and ergosterol were investigated in 75 different lichen associations collected in Antarctica, Arctic Canada, boreal Sweden, and temperate/subtropical forests of Tenerife, South Africa and Japan. The lichens had various morphologies and represented seven photobiont and 41 mycobiont genera. Chl a, chitin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
122
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 42 publications
22
122
0
1
Order By: Relevance
“…The net carbon uptake model is not able to determine which of the simulated strategies correspond to nitrogen-fixing lichens and bryophytes because there are no clear correlations between the ability to fix nitrogen and the productivity of a lichen or bryophyte species [Palmqvist et al, 2002]. Instead, the model calculates a weighted average of the carbon uptake of all strategies.…”
Section: /2013gb004705mentioning
confidence: 99%
“…The net carbon uptake model is not able to determine which of the simulated strategies correspond to nitrogen-fixing lichens and bryophytes because there are no clear correlations between the ability to fix nitrogen and the productivity of a lichen or bryophyte species [Palmqvist et al, 2002]. Instead, the model calculates a weighted average of the carbon uptake of all strategies.…”
Section: /2013gb004705mentioning
confidence: 99%
“…Finally, Poorter et al (2012) showed that carbon partitioning acclimates to different habitat conditions and patterns of assimilate allocation are known to serve as excellent indicators for growth performance in vascular plants. Palmquist et al (2002) propose that lichens are able to optimise their resource investments between carbohydrate input and expenditure, suggesting that a carbon economy view might be a fruitful way to compare and understand the performance of different lichens. An acclimation of resource allocation was suggested to be related to environmental conditions (Palmquist et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding this view, a link has been observed between lichen respiration and photosynthetic capacity (Palmqvist et al, 2002). The mechanisms underlying this are unclear, but lichen species with low photosynthetic capacity tend to have low respiration rates and vice versa (Palmqvist, 2000;Palmqvist et al, 2002). Our results suggest that a similar phenomenon may occur within a species.…”
Section: Differential Dark Respiration Among Treatments and Seasonsmentioning
confidence: 63%
“…In lichens, it is assumed that dark respiration is mainly attributed to fungal respiration because the mycobiont makes up the majority of the thallus (Palmqvist, 2000;Lange and Green, 2005). Notwithstanding this view, a link has been observed between lichen respiration and photosynthetic capacity (Palmqvist et al, 2002). The mechanisms underlying this are unclear, but lichen species with low photosynthetic capacity tend to have low respiration rates and vice versa (Palmqvist, 2000;Palmqvist et al, 2002).…”
Section: Differential Dark Respiration Among Treatments and Seasonsmentioning
confidence: 99%